Experimental Investigation of the Thermofluid Characteristics of Shell-and-Plate Heat Exchangers - Howard Lee; Ali Sadeghianjahromi; Po-Lun Kuo; Chi-Chuan Wang (Energies, 2020)
An experimental study regarding the thermofluid characteristics of a shell-and-plate heat exchanger with different chevron angles (45°/45°, 45°/65°, and 65°/65°) with a plate diameter of 440 mm was carried out. Water was used as the working fluid on both sides and the corresponding temperatures ranged from 30–70 °C. The flow rate on the plate or shell side ranged from 10–60 m3/h. The effects of chevron angles on the heat transfer and fluid flow characteristics of shell-and-plate heat exchangers were studied in detail. With regard to the heat transfer performance on the plate side, a higher chevron angle (65°/65°) resulted in a significantly better performance than a low chevron angle (45°/45°). The effect of the chevron angle became even more pronounced at high Reynolds numbers. Unlike the plate side, an increase in the chevron angle had a negative effect on the heat transfer performance of the shell side. Additionally, this opposite effect was more prominent at low Reynolds numbers due to the comparatively large contribution of the manifold. The friction factor increased appreciably with the increase in the chevron angle. However, when changing the chevron angle from 45°/45° to 65°/65°, the increase in the friction factor was about 3–4 times on the plate side while it was about 2 times on the shell side. This can be attributed to the presence of the distribution/collection manifold on the shell side. Empirical correlations for the Nusselt number and friction factor were developed for different combinations of chevron angles with mean deviations of less than 1%.